Efficacy of MAVIG X-Ray Protective Drapes in Reducing CTO Operator Radiation - Keir McCutcheon; Maarten Vanhaverbeke; Jérémie Dabin; Ruben Pauwels; Werner Schoonjans; Walter Desmet; Johan Bennett (Journal of Interventional Cardiology)
Background. The MAVIG X-ray protective drape (MXPD) has been shown to reduce operator radiation dose during percutaneous coronary interventions (PCI). Whether MXPDs are also effective in reducing operator radiation during chronic total occlusion (CTO) PCI, often with dual access, is unknown. Methods. We performed a prospective, randomized-controlled study comparing operator radiation dose during CTO PCI (n = 60) with or without pelvic MXPDs. The primary outcomes were the difference in first operator radiation dose (μSv) and relative dose of the first operator (radiation dose normalized for dose area product) at the level of the chest in the two groups. The effectiveness of MXPD in CTO PCI was compared with non-CTO PCI using a patient-level pooled analysis with a previously published non-CTO PCI randomized study. Results. The use of the MXPD was associated with a 37% reduction in operator dose (weighted median dose 26.0 (IQR 10.00–29.47) μSv in the drape group versus 41.8 (IQR 30.82–60.59) μSv in the no drape group; P<0.001) and a 60% reduction in relative operator dose (median dose 3.5 (IQR 2.5–5.4) E/DAPx10−3 in the drape group versus 8.6 (IQR 4.2–12.5) E/DAPx10−3 in the no drape group; P=0.001). MXPD was equally effective in reducing operator dose in CTO PCI compared with non-CTO PCI (P value for interaction 0.963). Conclusions. The pelvic MAVIG X-ray protective drape significantly reduced CTO operator radiation dose. This trial is clinically registered with https://www.clinicaltrials.gov (unique identifier: NCT04285944).